ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PADI ORGANIK DI KECAMATAN HARAU - Mukhlis Mukhlis; Raeza Firsta Wisra; Riva Hendriani; Nila Sari (AGRIBIOS, 2023)
Excessive use of chemical fertilizers causes a decrease in soil quality so that rice production decreases, even though the production costs incurred by farmers continue to increase due to the increasing price of chemical fertilizers. The purpose of this study was to determine what factors affect the income of organic rice farmers. This study used a survey method, where the determination of the research area was carried out deliberately and selected Nagari Koto Tuo Harau District. Determination of research samples using proportional stratified random sampling method, where the number of samples is 25 farmers. Data collection is done by interview and direct observation. Data analysis method used is kunatitatif analysis using multiple linear regression analysis. The results showed that the factors that significantly affect the income of organic rice farmers are land area, production costs, the amount of rice production and the price of rice. While the factors that affect insignificantly are age, education and other jobs. Keywords: Analysis, rice, organic, Yield